Comparison of Different DNA Sampling and Extraction Protocols for Bacterial and Archaeal Populations Analysis in Water Buffalo - La Mantia, Maria Chiara; Calì, Massimo; Rossi, Emanuela; Zilio, David Meo; Santangelo, Enrico; Chiariotti, Antonella (Journal of Buffalo Science, 2024)
Methane (CH4) is a potent greenhouse gas, and ruminants are a significant source of agricultural emissions. It has been hypothesized that the host’s genome controls rumen microbial communities, but robust results require numerous samples. The feasibility of a research project will depend on the ease and representativeness of the sampling method, as well as the cost-efficiency of large-scale sequencing. This study aimed to compare different protocols to investigate whether non-invasive samples could serve as a substitute for ruminal digesta. DNA recovery was tested in various matrices (whole rumen content, feces, and buccal swabs) from five cannulated buffalo cows. Three types of buccal swabs were tested, as well as feces in different forms (as-is, pelleted, or in a glycerol solution) and the rumen content. The study compared different protocols for DNA extraction, including WUR protocol, Maxwell®, and Quick Extract™, and two sampling times. Saliva was a challenging matrix to process, obtaining unsatisfactory DNA yield. Feces showed higher yields when pelleted but lower than rumen. The highest amount of DNA was obtained from whole rumen content using all three DNA extraction methods. Quick Extract was the easiest method to perform, while WUR resulted in the highest yield of DNA, swabs excluded. The Maxwell® method gave satisfactory results with all three matrices. However, further metagenomic analysis is required to verify if the species composition is comparable.